Congenital Granular Cell Tumor: Case Report and Review - Preston Gardner; Arlene Rozzelle (Hindawi Limited, 2018)
Congenital granular cell tumors are infrequently occurring masses occurring on a neonate's gingiva/alveolus. These lesions are benign with no noted malignant transformation, and treatment of excision is based on its effect on the neonate's respiratory ability and/or nutritional intake. The purpose of this review is to discuss a case of a congenital granular cell tumor and its treatment and review of the literature including demographics, histopathology, and operative treatment.